Necrotizing enterocolitis in low birth weight infants in China: Mortality risk factors expressed by birth weight categories - Tian Qian; Rong Zhang; Li Zhu; Peng Shi; Jie Yang; Chang-yi Yang; Dong-mei Chen; Jing-yun Shi; Xiao-guang Zhou; Yin-ping Qiu; Yong Yang; Ling He; et al. (Elsevier, 2017)
Background: We retrospectively investigated incidence, morbidity, and mortality of neonatal necrotizing enterocolitis in China, with special emphasis on determining the predictors of necrotizing enterocolitis associated mortality. Methods: We identified neonates as having necrotizing enterocolitis if they met the accepted diagnostic criterion. Data pertaining to antenatal period, labor and birth, and the postnatal course of illness were collected. Multivariate analysis and logistic regression were used to analyze the risk factors. Results: There were 1167 cases of necrotizing enterocolitis identified from the 95 participating NICUs in mainland China in 2011, with the incidence of 2.50% and 4.53% in LBW (birth weight <2500Â g) and VLBW (birth weight <1500Â g) infants, respectively. Stage 1, 2 and 3 diseases were noted in 51.1%, 30.3% and 18.6% of cases respectively. The mortality from stage 2 and 3 necrotizing enterocolitis in this cohort was 41.7%. In VLBW infants, the important risk factors for mortality were small for gestation age (OR: 5.02, 95% CI 1.73â14.6; PÂ =Â 0.003) and stage 3 NEC (OR: 8.09, 95% CI 2.80â23.3, PÂ <Â 0.001). In moderate LBW infants (birth weight 1500â2499Â g), the risk factors identified for mortality were sepsis during hospitalization (OR: 2.59, 95% CI 1.57â4.28, PÂ <Â 0.001) and stage 3 NEC (OR: 5.37, 95% CI 3.24â8.90; PÂ <Â 0.001). Conclusions: Necrotizing enterocolitis remains an important cause of morbidity and mortality in prematurely born neonates in Chinese neonatal units. Awareness of the associated risk factors and appropriate interventions may improve the outcome of necrotizing enterocolitis in different birth weight subgroup. Key Words: necrotizing enterocolitis, mortality, neonatology, prematurity, risk factor